Międzynarodowe instytucje finansowe a problem zadłużenia zagranicznego - Kosztowniak, Aneta (International Financial Institutions and the External Debt Problem, 2009)
The external debt problem has been existing in sharp form since 1980. Although this problem had not caused a sudden world crisis, its meaning is still growing and demanding long-lasting activities from a creditor countries side. The international financial institutions have undertaken many efforts to stop the debt problem on a large scale. The main goal of international financial institutions is to increase economic growth and improve abilities to pay off debt by indebted countries.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 156-163